Coping with English at university : students’ beliefs - Birna Arnbjörnsdóttir 1952-; Hafdís Ingvarsdóttir 1944- (2010)
The purpose of the research project presented here is to explore views of Icelandic university students on how the use of English affects their ability to master the curriculum, 90% of which is in English. Data was collected through electronic surveys of all students at the University of Iceland. The study asked (1) to what extent do students perceive that they are prepared to meet the demands of ac-cessing textbooks written in English, (2) what effect this has on the quality of their academic work, and (3) what strategies they use to negotiate meaning between the two linguistic codes they must use to master the curriculum. The results suggest that even though most students believe that they are prepared to study the curriculum in English, once probed, they say that working with two languages increases workload and that they employ various strategies to overcome the linguistic constraints posed by English textbooks. Tilgangur rannsóknarinnar var að kanna viðhorf nemenda við Háskóla Íslands til notkunar ensku en 90% kennslubóka við íslenska háskóla eru á ensku. Kannanir voru sendar til allra stúdenta við Háskóla Íslands og þeir spurðir 1) hversu vel undirbúnir þeir töldu sig vera til þess að læra námsefni á ensku, 2) hvaða áhrif það hefði á námið að námsefnið væri á ensku og 3) hvaða náms-aðferðir þeir notuðu til að tileinka sér námsefnið. Niðurstöður sýna að þó að stúdentar telji sig almennt vel undirbúna til að takast á við námsefni á ensku kemur í ljós að vinnuálag eykst og að þeir nota ýmsar leiðir til takast á við enskuna við tileinkun námsefnisins.